COLOUR,CULTURE,AND TRADITION OF INDIA IN THE POEMS OF SAROJINI NAIDU - Godbole, Vanashree (International Journal of Research -GRANTHAALAYAH, 2014)
Colour represents various moods of life. It is powerful means to communicate human feelings. Wide varied colours diversify each moment of our life. The sense of colour is as extended as the sense of LIFE. The folklore of a culture includes the stories, songs, and poems that people pass along from generation to generation. The word folklore meant “the Lore of the People.” It included all rituals, customs, traditions, and beliefs of unknown origin that expressed the concerns of the life ordinary people. Poetic imagery is a technique that is used to express feeling. In the visual, literary, and performing arts ‘Expressionism’ is a movement or tendency that strives to express subjective feelings and emotions rather than to depict reality or nature objectively. Sarojini Naidu was among the pioneer women poet, who was fascinated by the amazing diversity of Indian life, culture and tradition. Naidu. (1879 – 1949), was an Indian independence activist and poet. She was the second Indian woman to become the President of the Indian National Congress and was honored as ‘The Nightingale of India’ (Bharatiya Kokila). Being one of the most famous heroines of the 20th century, her birthday is celebrated as “National Women’s Day”. Naidu voiced the dreams and aspirations of the making of the nation. She wrote mainly on the rural i.e. the folk aspects of Indian culture and women’s experiences.